Highly frequent HIV-1 minority resistant variants at baseline of the ANRS 139 TRIO trial had a limited impact on virological response. (8th March 2015) - Charpentier, Charlotte; Lee, Guinevere Q.; Rodriguez, Christophe; Visseaux, Benoit; Storto, Alexandre; Fagard, Catherine; Molina, Jean-Michel; Katlama, Christine; Yazdanpanah, Yazdan; Harrigan, P. Richard; Descamps, Diane
Abstract: Objectives: To assess the prevalence of minority resistant variants (MRVs) at baseline and their impact on the virological response. The ANRS 139 TRIO trial evaluated the combination of raltegravir, etravirine and darunavir, plus an optimized background therapy, in 87% of cases. Patients were highly experienced and harboured multiresistant viruses, but were naive to the three drugs, and showed a high level of virological suppression. Methods: Ultra-deep sequencing of reverse transcriptase, protease and integrase regions was performed at the trial baseline, and sequences were interpreted according to the ANRS algorithm. MRVs were assessed using MiSeq and 454 technologies (limit of detection 1%). Results: At baseline, minority variants with at least one NRTI, one NNRTI, one PI, one major PI or an integrase inhibitor resistance-associated mutation were present in 46%, 45%, 68%, 24% and 13% of patients, respectively. When minority variants are taken into account, the prevalence of resistance to etravirine, darunavir and raltegravir at baseline was 29%, 40% and 9%, respectively. No difference was observed in the prevalence of MRVs between patients with virological failure and those with virological success, except a trend for patients exhibiting baseline etravirine MRVs (50% versus 26%, P  = 0.09). Conclusions: We have shown a high level of MRVs at baseline in highly pre-treated patients harbouring multiresistant viruses. However, these MRVs were not associated with an increased risk of virological failure, except for a trend for etravirine MRVs.